2003
DOI: 10.3346/jkms.2003.18.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Positive Trends of Public Attitudes Toward Epilepsy after Public Education Campaign Among Rural Korean Residents

Abstract: To assess trends of public attitudes toward epilepsy in Korea, two surveys were performed in the same village using a common questionnaire before and after the schedule of public education on epilepsy. Cross-sectional studies were conducted by means of a door-to-door interview, in which all residents over 19 yr of age living in the survey area were targeted. Vehicles for the educational campaign took the form of lectures and small group discussions. The understanding of epilepsy among Korean respondents appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
62
5
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 9 publications
3
62
5
8
Order By: Relevance
“…It has been clearly observed that the level of education infl uences the answers about the disease and leads to less pejorative attitudes to persons with epilepsy, corroborating with other researches designed for similar purposes 4,[6][7][8][9][10][11][13][14][15] . It is inferred that populations with a lower level of education and a lower income probably also have less access to information concerning epilepsy and this contributes to maintaining erroneous concepts about the disease.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It has been clearly observed that the level of education infl uences the answers about the disease and leads to less pejorative attitudes to persons with epilepsy, corroborating with other researches designed for similar purposes 4,[6][7][8][9][10][11][13][14][15] . It is inferred that populations with a lower level of education and a lower income probably also have less access to information concerning epilepsy and this contributes to maintaining erroneous concepts about the disease.…”
Section: Discussionsupporting
confidence: 62%
“…Questionnaires that evaluate the perception of epilepsy in many different social segments have been used by a great number of authors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Although many limitations have been observed such as understanding the questions, diffi culty in achieving the right answer since there is a broad range of epilepsies, the tendency is to not expose negative positions on the subject and the non-validation of the instrument 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population based surveys show that knowledge of epilepsy is generally superior among people with higher socioeconomic status and better educated individuals (university and grad school students). It has also been evaluated through a variety of studies that, in comparison, health care students of various countries in the world (Brazil, India, Italy, Canada) have more knowledge of epilepsy [12,13,14,15,16]. In our study we interviewed, 90 males & 180 females of a public sector medical college, in which 85.1% students consider epilepsy as a neurological disease as compared to a study performed on undergraduate medical students of Brazil, where 93.4% consider epilepsy as a brain disease [16], and an Indian study showed students who consider epilepsy as a neurological disease by 93.1% [11].…”
Section: Discussionmentioning
confidence: 99%
“…This may affect quality of life and psycho-social adjustment of people with epilepsy [1][2][3][4] . Misinformation and negative attitudes towards epilepsy are common over the world and contribute to discrimination against people with epilepsy 5,6 . These psycho-social difficulties are often considered more stressful and harmful than seizures themselves [7][8][9][10] .…”
mentioning
confidence: 99%